Protonated Diamines as Linkers in the Supramolecular Assemblies Based on the [V12b18o60h6] Polyoxovanadoborate Anion - Costamagna-Martra, J; Costamagna-Martra, J; Venegas-Yazigi, D; Venegas-Yazigi, D; Hermosilla-Ibanez, P; Hermosilla-Ibanez, P (Maik Nauka Publishing / Springer SBM, 2014)
Two new polyoxovanadoborates based crystalline lattices are being reported: K5(H3O)2(1,3-diapH2)2[V12B18O60H6]·10.80H2O (1), and K2(H3O)7(enH2)[V12B18O60H6]·9H2O (2). These structures are characterized by presenting multiple hydrogen bonds between the diprotonated diamines (enH2 and 1,3-diapH2) and hydronium ions, and the oxygen atoms of the [V12B18O60H6] cluster. The crystalline packing and stability of these new polyoxovanadoborates is dominated by the different types of hydrogen interactions present in the lattices ranging from unidirectional to trifurcated ones. The crystallographic data, together with the BVS method, permit to assign a mixed valence ratios for the [V12B18O60H6] anionic cluster for (1) and (2) being 11/1 (VIV/VV) ratio. © 2014 Pleiades Publishing, Ltd.